2002
DOI: 10.1021/jf011139b
|View full text |Cite
|
Sign up to set email alerts
|

Development and Application of an Indirect Competitive Enzyme-Linked Immunoassay for Aflatoxin M1 in Milk and Milk-Based Confectionery

Abstract: High-titer rabbit polyclonal antibodies to aflatoxin M(1) (AFM1) were produced by utilizing AFM1-bovine serum albumin (BSA) conjugate as an immunogen. An indirect competitive enzyme-linked immunosorbent assay was standardized for estimating AFM1 in milk and milk products. To avoid the influence of interfering substances present in the milk samples, it was necessary to prepare AFM1 standards in methanol extracts of certified reference material (CRM) not containing detectable AFM1 (< 0.05 ng/g). The reliability … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(42 citation statements)
references
References 13 publications
0
40
0
Order By: Relevance
“…However, milk and dairy products are the most potent source of aflatoxin among foods. AFM 1 intake, even at trace concentrations, causes a significant risk to human health, especially to infant and children who are the major consumers of infant formulas and milk (19,47,56). Although, The Joint FAO/WHO Expert Committee on Food Additives (JEFCA) did not establish a tolerable daily intake (TDI) for aflatoxins, strongly recommended that the level of aflatoxin should be kept as low as possible (43).…”
Section: Discussionmentioning
confidence: 99%
“…However, milk and dairy products are the most potent source of aflatoxin among foods. AFM 1 intake, even at trace concentrations, causes a significant risk to human health, especially to infant and children who are the major consumers of infant formulas and milk (19,47,56). Although, The Joint FAO/WHO Expert Committee on Food Additives (JEFCA) did not establish a tolerable daily intake (TDI) for aflatoxins, strongly recommended that the level of aflatoxin should be kept as low as possible (43).…”
Section: Discussionmentioning
confidence: 99%
“…Each of the five kits was singularly evaluated and compared with the other, emphasising strong limitations in some of them. Immunoassay techniques which regard AFM1 determination in milk have been also reported in literature (Pestka et al, 1981;Tihrumala-Devi et al, 2002;Magiulo et al, 2005), while few papers report results aimed at demonstrating that immunoassays are reliably applicable for measuring AFM1 in dairy products: examples are represented by the work of Kim et al who demonstrated the applicability of the developed ELISA in yogurt samples (Kim et al, 2000) and of a previously published work of our group where the modification of a commercial ELISA intended for milk analysis for measuring AFM1 in cheese was described (Anfossi et al, 2008). On the other hand, commercial ELISA kits have been widely used to study the fate of AFM1 during cheese-making or the occurrence of the toxin in various cheeses by several authors.…”
Section: Rapid Techniques For Measuring Afm1 In Cheesementioning
confidence: 91%
“…As IAC methods, these assays involve antigen-antibody specific interactions at the surface of various supports. Previously conventional enzyme immunoassay for aflatoxin analysis use antibodies immobilized on well polystyrene microtiter plates: they are based on a competitive process involving antigen and antigen labelled with an enzyme (horseradish peroxidase, generally) and on colorimetric detection with chromogenic substrates (Thirumala-Devi et al, 2002). Enzyme-linked immunosorbent assay is the best established and the most available immunoassay in aflatoxin rapid detection, using the 96 well plate microtiter format.…”
Section: Immunological Methodsmentioning
confidence: 99%
“…The development of these immunochemical methods and their evolution from single to multiple analyte screening, including topics on ELISA, immunosensors, fluorescence polarization and rapid visual tests (lateral-flow, flow-through and dipstick) have been developed. In literature there are many applications to aflatoxins analysis by ELISA: AFB1 determination in deep-red pepper (Ardic et al, 2008), which requires a clean-up by IAC prior ELISA test; many commercial AFB1 screening test in feedstuffs often without purification; AFM1 in milk (Fremy & Chu, 1984;Thirumala-Devi et al, 2002), that needs only defatting step prior to analysis, resulting in a useful screening test for routine quality control of milk of different farms before mixing the different milk bulks, especially when the absence of AFM1 above the regulatory limit needs to be documented. Enzyme labels can be detected also by chemiluminescent substrates, such as the luminol/peroxide/enhancer system for horseradish peroxidase (HRP) or dioxetane-based substrates for alkaline phosphatase, resulting in a very sensitive detection system in immunoassay.…”
Section: Immunological Methodsmentioning
confidence: 99%